Fungal community remediate quartz tailings soil under plant combined with urban sludge treatments - Dong, Fabao; Zhu, Yujia; Zhu, Xunmei; Zhang, Chengzhi; Tao, Yingying; Shao, Taotao; Wang, Yue; Luo, Xia (Frontiers in Microbiology, 2023)
Tailings can cause extensive damage to soil structure and microbial community. Phytoremediation is an effective strategy for remedied tailings soil due to its environmentally friendly and low-cost advantage. Fungi play a crucial role in nutrient cycling, stress resistance, stabilizing soil structure, and promoting plant growth. However, the fungal community variation in phytoremediation remains largely unexplored. Here, we analyzed soil fungal community based on high-throughput sequencing during three plant species combined with urban sludge to remediate quartz tailings soil. The results indicated that the fungal diversity was significantly increased with plant diversity, and the highest fungal diversity was in the three plant species combination treatments. Moreover, the fungal diversity was significantly decreased with the addition of urban sludge compared with plant treatments, while the abundance of potential beneficial fungi such as Cutaneotrichosporon, Apiotrichum, and Alternaria were increased. Notably, the fungal community composition in different plant species combination treatments were significant difference at the genus level. The addition of urban sludge increased pH, AP and AN content that were the main drivers for fungal community composition. Furthermore, the fungal networks of the plant treatments had more nodes and edges, higher connectedness, and lower modularity than plant combined with urban sludge treatments. Collectively, our results showed that three plant species combined with urban sludge treatments improved fungal community and soil properties. Our results provide insights for quartz tailings soil remediation using plant-fungi-urban sludge.